The Relationship between Principal Academic Supervision, School Culture and Teacher Professionalism on Teacher Performance in Wonocolo District Elementary School - Erlisa, Dyan; Amalia, Kaniati; Haq, Mohammad Syahidul; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the relationship between principals’ academic supervision, school culture, and teacher professionalism on teacher performance in public elementary schools in Wonocolo District. A quantitative approach with a correlational design was employed. The population consisted of all elementary school teachers in Wonocolo District, and the sample was selected using proportional random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and multiple regression analysis. The results indicate that principals’ academic supervision has a significant relationship with teacher performance. School culture is also significantly related to teacher performance, while teacher professionalism shows a significant influence on teacher performance. Furthermore, academic supervision, school culture, and teacher professionalism simultaneously have a significant relationship with teacher performance. These findings suggest that improving teacher performance requires integrated efforts through effective academic supervision, the development of a positive school culture, and continuous professional development. This study contributes theoretically to educational management literature and provides practical implications for school leaders and policymakers in enhancing the quality of elementary education.